Study of TiC cutting tool insert using microwave synthesis - Thauri, Shahdura Hammad; Mohamed Ariff, Tasnim Firdaus; Karim, A.N. Mustafizul (Trans Tech Publications Ltd., Switzerland, 2011)
Microwave processing ceramics is emerging fast as a new field of ceramic processing and material synthesis. The past year has witnessed significant progress in the aspects of commercialization and application of the technology to new areas. Further research states that Titanium Carbide (TiC) is the best cutting tool due to its high melting point and by that reason this project aims to show the difference between conventional sintering, microwave sintering and Hot Isostatic Pressing (HIP). Two different compositions consisting of 97TiC3Ni and 93TiC7Ni were sintered using conventional furnace, microwave furnace and HIP. Density, hardness and microstructure analysis were carried out on these TiC inserts. 97TiC3Ni produced higher density and hardness values compared to 93TiC7Ni for all three different methods. Microwave sintering produced the highest density and hardness values compared to conventional sintering and HIP. Microwave produced samples with improved density and hardness in a shorter processing time which is 93% faster than conventional sintering and 50% faster than HIP.